Increased mortality risk in people with schizophrenia in Lithuania 2001–2020 - Mingaile Drevinskaite; Auguste Kaceniene; Arunas Germanavicius; Giedre Smailyte (Schizophrenia)
Abstract The aim of this study was to assess mortality risk in people with schizophrenia in Lithuania from 2001 and 2020. Cause-specific and all-cause mortality risk among patients with schizophrenia was assessed using a retrospective cohort study design. The cohort identified all patients with schizophrenia diagnosis (ICD-10 code F20) who were admitted to the Vilnius Republican Psychiatric Hospital from 1 January, 2001 to December 31, 2020. Dates of death and emigration were obtained from the Central Population Register. The standardized mortality ratios (SMRs) were calculated by dividing the observed number of deaths among patients with schizophrenia by the expected number of deaths, calculated using the national rates. The final cohort included 7883 patients, with 2458 observed deaths. An increased all-cause mortality risk was found for both sexes (SMR = 1.96; 95% CI 1.88–2.04) compared to the general population. The most common cause-specific mortality risk was found for diseases of the circulatory system (SMR = 2.17; 95% CI 2.05–2.30). Other significant increases in cause-specific mortality risk were observed for infectious diseases, mental and behavioural disorders, diseases of the nervous system and respiratory system, diseases of the genitourinary system, as well as external causes. Patients with schizophrenia do not benefit from the health strategies that have led to reduced mortality in the general population. To close the mortality gap, smoking and alcohol cessation interventions, cardiovascular and cancer screening and monitoring, early diagnosis, and interventions for identified physical diseases should be regarded as imperative.